1994
DOI: 10.1111/j.1346-8138.1994.tb01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Studies of Infiltrating Cells in Early and Chronic Lesions of Psoriasis

Abstract: The expression of surface antigens on infiltrating cells, epidermal keratinocytes, and dendritic cells in biopsy specimens from 31 patients with psoriasis was examined immunohistochemically. The specimens were divided into early-phase and chronic-phase groups and then examined in a double blind manner. Among the infiltrating cells in the epidermis, CD4-positive cells were dominant in the early phase; CD8-positive cells were dominant in the chronic phase, resulting in a markedly decreased CD4/CD8 ratio in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
2
32
3
Order By: Relevance
“…Immunohistochemical analysis of different stages of cellular infiltrate development in psoriasis showed a higher number of CD1a+ cells in chronic changes [24], but there are also studies which support the hypothesis of increased LCs density in early changes [21].…”
Section: Discussionmentioning
confidence: 82%
“…Immunohistochemical analysis of different stages of cellular infiltrate development in psoriasis showed a higher number of CD1a+ cells in chronic changes [24], but there are also studies which support the hypothesis of increased LCs density in early changes [21].…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that the proteolytic actions performed by CATS within early endosomes of most of the professional APCs comprise degradation of MHC class II-associated invariant chain (1,8,27). Given this function, the upregulation of MHC class II-immunoreactivity in the psoriatic epidermis reported in this study and the ability of keratinocytes to synthesize MHC class II (16,30,58,59) we addressed the question whether CATS fulfills similar tasks in keratinocytes. Using a specific CATS inhibitor we showed that CATS has a distinct role in Ii processing as well as in MHC class II expression in keratinocytes.…”
Section: Discussionmentioning
confidence: 85%
“…Taking into consideration the importance of immunological aspects in pathogenesis of psoriasis [8, 17, 18, 19, 20, 21], these results represent a promising basis for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies indicate the involvement of immunomodulating or immunosuppressive effects. Immunological changes could be observed both locally in psoriatic plaques [7, 8] as well as systemically [4, 9]. More detailed statements, particularly in long-term observations, are not available at the present.…”
Section: Introductionmentioning
confidence: 99%